Electronic propinquity in the hospital management system among ICT integrated hospitals in Malaysia - Nik Adzrieman Abd Rahman, (Penerbit Universiti Kebangsaan Malaysia, 2017)
This research explores the applicability of electronic propinquity (EP) in hospitals and the integrated communication among medical doctors in Malaysia by utilizing new media facilities. This research uses and updates Korzenny’s (1978) electronic propinquity theory. A total of six hospitals were selected in this study. This study used a qualitative methodology to address all objectives: to examine the level of IT literacy among Medical Officers; to examine the existence of electronic propinquity among medical officers; to explore the use of new media among medical staffs in their work and to identify the integrated communication among medical officers. For this purpose, the formula introduced by Amran Rasli has been adopted to examine the IT literacy level of medical officers. To obtain an applicable result, 8 Medical Officers agreed to take part in semi-structured interviews and to fill in the forms provided. From the result of this analysis and through thematic methods, we found that the advantages listed are contained in the elements of EP. The study showed that the level of literacy among Medical Officers is high, and the most used programme is the Microsoft Words. The study also showed that there is an existence of electronic near-theoretical in hospital management which uses new media preordained by the closeness in time, followed by physical and distance. Among other purpose of using new media among medical officers is to gain knowledge, office work and entertainment. Finally, the result of this study showed that the integrated communication existed indirectly. Regardless that the ICT facilities are provided by the Malaysian government, the use of applications in mobile phones is considered more helpful to the Medical Officer to carry out their responsibilities. This statement is in line with some previous research findings, medical doctors need only a few technology-oriented facilities in management since their primary task is to treat patients while only a few are involved with administrations.